Nursing diagnoses related to the sexuality of elderly: contributions to practice - Souza Júnior, Edison Vitório de (2021)
Aim: Considering the growing population ageing and the scientific evidence that sexuality in the elderly population is not frequently addressed by health services, the present study contributes significantly to nursing practices. The aim of this study was to identify in the literature situations related to the sexuality of elderly citizens and draw nursing diagnoses with the theoretical support of the North American Nursing Diagnosis Association (NANDA 2018-2020). Methods: It is an integrative review of the literature constructed from 15 systematically selected original articles; these were retrieved from VHL, SciELO, Pubmed, Lilacs, BDENF, IBECS, ScienceDirect, Scopus, Web of Science and Google Scholar. Results: A total of 29 diagnostics were traced in the following domains: health promotion 3 (10.3%); activity / rest 3 (10.3%); perception / cognition 4 (13.9%); self-perception 5 (17.2%); roles and relationships 2 (6.9%); sexual disorder 1 (3.4%); coping / tolerances up to 3 (10.3%); principles of life 2 (6.9%); security / protection 4 (13.9%) and comfort 2 (6.9%). The domain “self-perception” was the domain that presented more evidence in the studies. Conclusion: This makes one reflect on the power that each individual has acquired through the evolution of the entire social-political situation which at different times shapes the beliefs, attitudes and behaviors of the population. It has been drawn to the attention of nursing professionals that they must pay more attention to the aspects that permeate the subjectivity and personal values ​​of elderly citizens, and, through this study, there will be the direction and ease of assistance in the face of sexuality of this age group.